2012
DOI: 10.1037/a0030385
|View full text |Cite
|
Sign up to set email alerts
|

Persons, situations, and behaviors: Consistency and variability of different behaviors in four interpersonal situations.

Abstract: Understanding how persons, situations, and behaviors contribute to behavioral consistency is a central goal for the science of behavior. The present study focused on dyadic social situations that were created by professional actors who enacted 4 social roles derived from interpersonal theory: dominant, submissive, agreeable, and quarrelsome. A total of 128 behavioral episodes from 32 target participants who each interacted for 5 min with 4 same-sex actors were videotaped. Several behaviors were coded from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 71 publications
2
55
0
2
Order By: Relevance
“…However, “warm” does not specify the specific actions, such as whether he or she smiled, slapped someone on the back, or shared dessert. Rather, it evaluates the meaning of the behavior (Leikas et al, 2012; Sherman et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, “warm” does not specify the specific actions, such as whether he or she smiled, slapped someone on the back, or shared dessert. Rather, it evaluates the meaning of the behavior (Leikas et al, 2012; Sherman et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, researchers have used concrete behaviors (e.g., slapped someone on the back) to assess trait enactments (Jackson et al, 2010; Leikas et al, 2012; Wu & Clark, 2003). However, there is ambiguity in identifying the trait content a given concrete behavior is enacting.…”
Section: How To Measure Behavior In Order To Assess Variability?mentioning
confidence: 99%
See 1 more Smart Citation
“…This result is notable in light of previous studies that have consistently shown that behaviour is jointly determined by the interaction of personality and situational variables (cf. Snyder & Cantor, ), in the sense that the expression of personality differences depends on certain situational features (for some notable examples, see Leikas et al, ; Sherman et al, ; also see Balliet & Van Lange, ). It is important to note, however, that the lack of person–situation interaction effects that was observed in the present study should only be interpreted in the context of the specific variables that were included in our study and by no means imply that such interactions cannot occur if other personality and situational variables are taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a large body of prior research has employed a person × situation approach to study human behaviour (Snyder & Cantor, ), and these studies were conducted in both experimental (e.g. Leikas, Lönnqvist, & Verkasalo, ) and field settings (e.g. Sherman, Rauthmann, Brown, Serfass, & Jones, ).…”
Section: Consistency In Choice Behaviour In Mixed‐motive Gamesmentioning
confidence: 99%